Trauma outcomes in nonfatal road traffic accidents: a Portuguese medico-legal approach - Flávia Cunha-Diniz; Tiago Taveira-Gomes; José Manuel Teixeira; Teresa Magalhães (Oxford University Press, 2022)
The objective of this study was to compare the outcomes of nonfatal road traffic accidents by the victims' age group and sex. We used the Portuguese medico-legal rules for personal injury assessment, in the scope of the Civil Law in that country, which includes a three-dimensional methodology. This was a retrospective study including 667 victims of road traffic accidents aged 3-94 years old. Their final medico-legal reports all used the Portuguese methodology for personal injury assessment. Outcomes were analysed by the victims' age group (children, working-age adults, and older people) and sex. Road traffic accidents were generally serious (ISS mean 9.5), with higher severity in children and older people. The most frequent body sequelae were musculoskeletal (64.8%), which were associated with functional and situational outcomes. Temporary damage resulted in an average length of impairment of daily life of 199.6 days, 171.7 days to return to work, and an average degree of quantum doloris (non-economic damage related to physical and psychological harm) of 3.7/7. The average permanent damage was 7.3/100 points for Permanent Functional Deficit, 0.43/3 for Permanent Professional Repercussion, 2/7 for Permanent Aesthetic Damage, 3.9/7 for Permanent Repercussion on Sexual Activity and 3.2/7 for Permanent Repercussion on Sport and Leisure Activities. Overall, 19% of people became permanently dependent (10.6% needed third-party assistance). The medico-legal methodology used, considering victims' real-life situation, allows a comprehensive assessment. There were several significant differences among the three age groups but none between sexes. These differences and the impact of the more severe cases justify further detailed medico-legal studies in these specific situations on children, older people, and severely injured victims.Key points:This was a retrospective study of accident mechanisms and injury outcomes in Portugal, and considered the outcomes in the victims' real-life situation.Lesions from road traffic accidents were generally serious, with higher severity among children and older people.The most frequent sequels were musculoskeletal, and associated with functional and situational outcomes.Both temporary and permanent outcomes had repercussions for the victims.There were significant differences between children, working-age adults and older people, but none between sexes.